Relationship of Oral Health Literacy with Dental Caries and Oral Health Behavior of Children and Their Parents - Reza Yazdani; Ehsan NasrEsfahani; Mohammad Javad Kharazifard (Tehran University of Medical Sciences, 2018)
Objectives: This study sought to assess the relationship of oral health literacy (OHL)of the parents with DMFT index ofthemselves and their children. Materials and Methods: This cross-sectional study was performed on 258 children presenting to the Pediatric Dentistry and Orthodontics Departments of XXX in 2016 along with their parents. The parents were asked to fill out the OHL questionnaire, the validity and reliability of which had been previously confirmed in the Iranian and non-Iranian populations. Also, both parents and children were clinically examined to determine their DMFT index according to the WHOcriteria. Backward linear regression model was applied to assess the effect of demographic factors on OHL, behavioral habits and DMFT. The Pearson's bivariate correlation was used to assess the relationship of OHL, behavioral habits and health indices. Results: A significant linear correlation was noted between OHL of the parents with (f) in children. Only 48.5% of parents had adequate OHL. Children whose parents had adequate OHL had a significantly higher (f) and lower (m). Children whose parents had inadequate or marginal OHL had significantly lower (f) and higher (m). Conclusion: Higher OHL of the parents significantly improves the DMFT index of themselves and their children and enhances their oral health behavior. Thus, programs must be implemented in developing countries like Iran to promote the OHL of the parents and consequently improve the oral health status of children.